Nuovi strumenti di telerilevamento da satellite nel controllo del territorio - Dussi, Michele (GEOmedia, 2008)
New satellite remote sensing instruments for land management COSMO-Skymed remote sensing images, as well as other SAR (Synthetic Aperture Radar) missions, have their specific features, partly similar to optical system products.Pre-processing activities, allow the user to exploit the systems capabilites fairly easily after a focused training. SAR imaging's applications range from mission-critical applications (i.e. civil and military security applications) to simple user-driven ones (i.e. qualitative upgrade of civil cartography). In this application range, there is room for much development and optimization using new Cosmo- Skymed products. The best way to proceed seems to be tailoring single "vertical" application at a time.